A Reconsideration of Michelangelo's Unrealised Façade for the Basilica of San Lorenzo in Florence. (2019) - Stine, Darin
Abstract: This article reconsiders Michelangelo's unrealised façade project for the church of San Lorenzo in Florence. While surviving evidence, particularly the extant wooden model preserved today in the Casa Buonarroti, gives a good indication of the façade's planned appearance, we are still unclear about how Michelangelo intended it to attach to the church. By reassessing surviving graphic and written sources for the commission, the article argues for a reconstruction of Michelangelo's design as a narthex. It draws further support from an analysis of the intended building site on Piazza San Lorenzo, which, due to its restricted space, suggests that only a narthex construction was possible. By envisaging the façade of the church as a narthex, Michelangelo may have intended it to function as a focal point for religious and civic ceremonies that took place in the piazza.